Shiga toxin 2-induced intestinal pathology in infant rabbits is A-subunit dependent and responsive to the tyrosine kinase and potential ZAK inhibitor imatinib - Stone, Samuel; Thorpe, Cheleste; Ahluwalia, Amrita; Rogers, Arlin; Obata, Fumiko; Vozenilek, Aimee; Kolling, Glynis; Kane, Anne; Magun, Bruce; Jandhyala, Dakshina (Frontiers in Cellular and Infection Microbiology, 2012)
Shiga toxin producing Escherichia coli (STEC) are a major cause of food-borne illness worldwide. However, a consensus regarding the role Shiga toxins play in the onset of diarrhea and hemorrhagic colitis is lacking. One of the obstacles to understanding the role of Shiga toxins to STEC-mediated intestinal pathology is a deficit in small animal models that perfectly mimic human disease. Infant rabbits have been previously used to study STEC and/or Shiga toxin-mediated intestinal inflammation and diarrhea. We demonstrate using infant rabbits that Shiga toxin-mediated intestinal damage requires A-subunit activity, and like the human colon, that of the infant rabbit expresses the Shiga toxin receptor Gb3. We also demonstrate that Shiga toxin treatment of the infant rabbit results in apoptosis and activation of p38 within colonic tissues. Finally we demonstrate that the infant rabbit model may be used to test candidate therapeutics against Shiga toxin-mediated intestinal damage. While the p38 inhibitor SB203580 and the ZAK inhibitor DHP-2 were ineffective at preventing Shiga toxin-mediated damage to the colon, pretreatment of infant rabbits with the drug imatinib resulted in a decrease of Shiga toxin-mediated heterophil infiltration of the colon. Therefore we propose that this model may be useful in elucidating mechanisms by which Shiga toxins could contribute to intestinal damage in the human.